PENINGKATAN KAPASITAS PRODUKSI TEH CELUP BUNGA TELANG MELALUI OPTIMALISASI SDM DI POSBINDU DAHLIA INDAH, PETUKANGAN SELATAN - Hamidah Dwiningtias; Didik Hariyadi Raharjo; Taqwa Putra Budi Purnomo Sidi Hiram (Jurnal Padamu Negeri, 2025)
Posbindu Dahlia Indah located in Petukangan Selatan Village has developed into a center for community empowerment activities based on local potential, especially in the production of tea bags from butterfly pea flowers (Clitoria ternatea). This product has added value both in terms of economy and health benefits, thus promising broad market opportunities. However, limitations in human resource (HR) management, such as lack of technical skills, suboptimal division of tasks, and minimal knowledge about packaging and marketing, are the main obstacles in increasing production and distribution capacity. This study aims to identify the main challenges in the production process and formulate empowerment strategies through HR training and optimization. The methods used include direct observation of production activities, focus group discussions (FGD) to explore problems and solutions from the perspective of group members, and skills training tailored to local needs. The training covers technical aspects of production, sanitation, packaging, and the basics of community marketing. The results of the study showed that training designed in a participatory manner was able to improve technical skills and self-confidence of group members. A more structured division of tasks also increased the efficiency of the production process. In addition, there is an increase in collective awareness of the importance of building local brands and utilizing social media as a means of promotion. This program not only has an impact on increasing production capacity, but also strengthens social ties between members and creates a spirit of community-based economic independence. This study recommends strengthening ongoing mentoring and expanding marketing networks as strategic steps to support the sustainability of the butterfly pea flower tea bag production business at Posbindu Dahlia Indah. The results of this study are expected to be a model for local economic empowerment that can be replicated in other communities with similar potential.